2011
DOI: 10.3382/ps.2010-01023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating and aging of poultry litter on the persistence of enteric bacteria

Abstract: Food-borne illnesses have rarely been associated with the reuse of poultry litter as an organic fertilizer and soil amendment in agriculture. Yet farming practices in many countries have come under increased scrutiny because of heightened consumer awareness of food safety and environmental issues. This study was conducted to determine whether simple on-farm management practices could improve the microbiological safety of poultry litter. First, the effects of heat and moisture on the survival of Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 21 publications
5
94
0
4
Order By: Relevance
“…There are many kinds of stress factors (environment, diseases, psychological factors and feeding management) in broiler breeding, which can directly or indirectly change the immune system, and induce the immune stress. (Mashaly et al 2004;Shini & Kaiser 2009;Wilkinson et al 2011) Previous studies showed that a number of different stressors result in the activation of the Hypothalamic-Pituitary-Adrenal axis (HPA axis) and the release of adrenocorticotropic hormone (ACTH), corticosterone (CORT) and the stressors can also act on immune system to influence organ growth, profiles of inflammatory cytokines and the immune response of antigen to antibody (Marketon & Glaser 2008;Shini & Kaiser 2009;Shini et al 2010). When under immune stress, animal body protein and fat anabolism will be weakened, while catabolism will be enhanced in order to satisfy the requirement of nutrients to synthesise immune effector molecules, and then animal will consume large amount nutrients, resulting in lower feed utilisation and decreased growth performance (Johnson 1997;Jacobi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There are many kinds of stress factors (environment, diseases, psychological factors and feeding management) in broiler breeding, which can directly or indirectly change the immune system, and induce the immune stress. (Mashaly et al 2004;Shini & Kaiser 2009;Wilkinson et al 2011) Previous studies showed that a number of different stressors result in the activation of the Hypothalamic-Pituitary-Adrenal axis (HPA axis) and the release of adrenocorticotropic hormone (ACTH), corticosterone (CORT) and the stressors can also act on immune system to influence organ growth, profiles of inflammatory cytokines and the immune response of antigen to antibody (Marketon & Glaser 2008;Shini & Kaiser 2009;Shini et al 2010). When under immune stress, animal body protein and fat anabolism will be weakened, while catabolism will be enhanced in order to satisfy the requirement of nutrients to synthesise immune effector molecules, and then animal will consume large amount nutrients, resulting in lower feed utilisation and decreased growth performance (Johnson 1997;Jacobi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…High temperature is the most frequently studied mechanism involved in the inactivation of human pathogens during organic waste treatment processes (2,4,26,31,38). For example, Wilkinson et al (38) reported that Salmonella Typhimurium in fresh chicken litter containing rice hulls (30, 50, or 65% of moisture) was completely eliminated within 1 h in a water bath at both 55 and 65°C.…”
mentioning
confidence: 99%
“…For example, Wilkinson et al (38) reported that Salmonella Typhimurium in fresh chicken litter containing rice hulls (30, 50, or 65% of moisture) was completely eliminated within 1 h in a water bath at both 55 and 65°C. Stringfellow et al (31) used pasteurization, with exposure to steam for 5, 30, or 120 min, to reduce Salmonella Typhimurium in chicken litter with pine shavings and found that Salmonella died off in chicken litter with 30 or 120 min of steaming, whereas a 3-log reduction was observed for 5 min of steaming.…”
mentioning
confidence: 99%
“…Consequently chickens can also be directly infected by water, feeds, rodents, flies and dust [9]. Poultry beddings are considered by some authors [10] as a hostile environment for the persistence of pathogens because it is dry, it has high ammonia content and it readily heats up. Research evidence suggests that bacterial counts decrease sufficiently when beddings are composted [11].…”
Section: Prevalence Of Bacteriamentioning
confidence: 99%